2011
DOI: 10.1111/j.1464-5491.2011.03383.x
|View full text |Cite
|
Sign up to set email alerts
|

Losartan and amlodipine on myocardial structure and function: a prospective, randomized, clinical trial

Abstract: Losartan provided a greater attenuation of left ventricular hypertrophy than amlodipine, seemingly as a result of a greater reduction of myocardial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…There was observed a significant reduction in values of interventricular septum, PWT, LV diastolic internal diameter, and LVMI in both losartan group and amlodipine group. Indexed LV mass reduced in both groups by 6 months; effects of reducing LVMI in losartan study group was found to be more effective than amlodipine study group, which was more comparable with the results of Fogari et al's study [20] (Table 5). …”
Section: Rutuparna Et Alsupporting
confidence: 81%
“…There was observed a significant reduction in values of interventricular septum, PWT, LV diastolic internal diameter, and LVMI in both losartan group and amlodipine group. Indexed LV mass reduced in both groups by 6 months; effects of reducing LVMI in losartan study group was found to be more effective than amlodipine study group, which was more comparable with the results of Fogari et al's study [20] (Table 5). …”
Section: Rutuparna Et Alsupporting
confidence: 81%
“…A total of 28 RCTs 13 – 40 with 2403 hypertensive patients were identified for inclusion from 6042 relevant publications. The flow of selecting studies for the meta-analysis was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Sample size of the studies ranged from 24 to 411 participants, totaling 2403 participants. 13 – 40 The average age ranged from 43.8 to 66.7 years, and men accounted for 23.7% to 100% in each study. The range of mean SBP at baseline was 144 to 189 mmHg, whereas the range of mean DBP was 86 to 106 mmHg.…”
Section: Resultsmentioning
confidence: 99%
“…Selectivity for nuclear GRK5 activity may also explain discrepancies in the success of current HF treatments targeting Gq-coupled GPCRs. For example, AT 1 R antagonists (ARBs) such as Losartan, demonstrate efficacy in reversing cardiac hypertrophy in humans [56], [57]. Although the effects of ARBs are thought to be at least partly due to decreased blood pressure and cardiac load, patients treated with Losartan have attenuated hypertrophy accompanied by reduced cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%